2001
DOI: 10.1108/09653560110403278
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of public perception of debris flow hazard

Abstract: Landslides are common occurrences in the US West. Some of these events cause injury and even death to visitors to these landscapes. Investigates changes in visitor perceptions of the likelihood and location of landslide events in Glacier National Park, Montana, in the wake of a series of hazardous debris flow occurrences. The initial surveying was completed at the Logan Pass Visitor Center on 17 July 1998 using a specially created survey. On 28 July 1998, a series of debris flows crossed Going‐to‐the‐Sun Road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Few studies on risk perception have been conducted thus far with regard to debris flows. As an example, DeChano and Butler (2001) found that in Glacier National Park, Montana, the occurrence of numerous debris flows, including some that trapped people in their cars, had not changed public perception of this type of mass movement. A study in Taiwan on how disaster characteristics influence risk perception showed that the main concern of flood victims is financial loss, whereas the main concern of landslide victims is human casualties (Ho et al 2008).…”
Section: Discussion On Public Perception and Stakeholder Involvementmentioning
confidence: 97%
“…Few studies on risk perception have been conducted thus far with regard to debris flows. As an example, DeChano and Butler (2001) found that in Glacier National Park, Montana, the occurrence of numerous debris flows, including some that trapped people in their cars, had not changed public perception of this type of mass movement. A study in Taiwan on how disaster characteristics influence risk perception showed that the main concern of flood victims is financial loss, whereas the main concern of landslide victims is human casualties (Ho et al 2008).…”
Section: Discussion On Public Perception and Stakeholder Involvementmentioning
confidence: 97%
“…The debris flows in the western sector of the promontory are particularly important in terms of geomorphological dynamics (Schumm, 1994;De Chano and Butler, 2001). Moreover, colluvial deposits covering the contact between the Flysch and the Conglomerate are found in the upper portions of this slope.…”
Section: Geomorphological Hazardmentioning
confidence: 99%
“…Nevertheless, during the last years, several research studies were also conducted in the field of natural hazard risk perception (e.g. Litai et al, 1983;Rogers, 1984;Fell, 1994;McDaniels et al, 1995McDaniels et al, , 1996Finlay and Fell, 1997;DeChano and Butler, 2001;Plapp, 2004;Siegrist et al, 2004).…”
Section: Problems Of a Risk-based Approachmentioning
confidence: 99%